2013
DOI: 10.1371/journal.pone.0076723
|View full text |Cite
|
Sign up to set email alerts
|

Does an ‘Activity-Permissive’ Workplace Change Office Workers’ Sitting and Activity Time?

Abstract: IntroductionTo describe changes in workplace physical activity, and health-, and work-related outcomes, in workers who transitioned from a conventional to an ‘activity-permissive’ workplace.MethodsA natural pre-post experiment conducted in Vancouver, Canada in 2011. A convenience sample of office-based workers (n=24, 75% women, mean [SD] age = 34.5 [8.1] years) were examined four months following relocation from a conventional workplace (pre) to a newly-constructed, purpose-built, movement-oriented physical en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
116
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(119 citation statements)
references
References 25 publications
0
116
3
Order By: Relevance
“…There are, however, strong indications that simply changing the office environment might not be enough to invoke long-term change in behaviour. Strategies and programmes for implementing change will need careful organisational and behavioural support and public education to prevent current interests in active office environments from simply being a passing fad 53 57 58. Similar to the risks of prolonged, static, seated positions, so too should prolonged, static, standing postures be avoided;59 movement does need to be checked and corrected on a regular basis especially in the presence of any musculoskeletal sensations 60.…”
Section: Sedentary Office Environmentsmentioning
confidence: 99%
“…There are, however, strong indications that simply changing the office environment might not be enough to invoke long-term change in behaviour. Strategies and programmes for implementing change will need careful organisational and behavioural support and public education to prevent current interests in active office environments from simply being a passing fad 53 57 58. Similar to the risks of prolonged, static, seated positions, so too should prolonged, static, standing postures be avoided;59 movement does need to be checked and corrected on a regular basis especially in the presence of any musculoskeletal sensations 60.…”
Section: Sedentary Office Environmentsmentioning
confidence: 99%
“…This conclusion is in line with a recent review and metaanalysis of 38 field and laboratory studies (30), showing that activity permissive workstations (mostly sit-stand workstations) led to a substantial reduction in sedentary time, with a pooled intervention effect of -77 minutes in an 8-hour workday. The evidence of an effect of alternative workstations on overall PA was conflicting, but subgroup analyses showed moderate evidence for a positive effect of treadmill workstations on overall PA; whereas the two studies using sit-stand workstations (47,53) did not find an effect on overall PA (table E). This adds to the conclusion of Tudor-Locke et al (29) that treadmill (and pedal) desks have the greatest potential to influence energy expenditure, with an effect that does not seem to be limited to working hours.…”
Section: Alternative Worktation Interventionsmentioning
confidence: 99%
“…Furthermore, we point to the need to understand effects on SB and PA of interventions that lie outside the three categories we found in the present literature. Examples are interventions such as job rotation and enrichment that redistribute tasks between workers or introduce new tasks in the job (85, 86) and interventions rebuilding the workspace, such as designing offices to promote PA (47,87,88) and furnishing offices with equipment facilitating standing and PA (89). In both cases, effects on SB and/or PA are likely.…”
Section: Implications For Practice and Future Researchmentioning
confidence: 99%
“…Occupation makes a difference in time spent sitting at work with offi ce workers (managers, clerks, and scientifi c and artistic professions) shown to sit signifi cantly longer than manual workers (agricultural, service, trade, industrial, transportation, and commercial) at work (Jans et al 2007 ). A natural experiment where participants moved from a conventional "closed-design" offi ce building to a modern building fostering movement (height-adjustable workstations for some, standing-option meeting rooms and common areas, centralized supplies/printing, and vertically integrated offi ce layout) found that sitting time (6 h/day before the move) was reduced by 20 min after the move (Gorman et al 2013 ). Type of work (deskbound or not) is obviously a major determinant of how long people sit in their workplace (Thorp et al 2012 ;van Uffelen et al 2012 ).…”
Section: Workplace Sedentary Behaviormentioning
confidence: 99%